The Influence of Managerial Ownership, Debt Covenant and Growth Opportunities on Accounting Conservatism - Lia yunita utami (Accounting and Finance Studies, 2021)
The aim of this research is to analyze the effect of accounting to the practice ofmanagerial ownership, debt covenant and growth opportunities on accountingconsevatism. The sample of this reseach is manufacture firm which is listed onindonesia stcok exchange (IDX) over 2011-2015. The research sample are 11 firmwith 55 observations. Technique of analyzing data used is the classic assumptiontest, test multiple linear regression analysis, and hypothesis testing using SPSStool.The results of the research as follow: (1) managerial ownership significant influenceto accounting conservatism (2) the debt covenance not significant influence toaccounting conservatism, (3) the growth opportunities not significant influence toaccounting consevatism (4) simultaneously, the result indicates that managerialownership, debt covenance, and growth opportunities does have an accountingconservatism